Singularities of Partially Polarized Vortex Beams - Raburn, William Scott; Gbur, Greg (Frontiers in Physics, 2020)
Singularities in the polarization state of nonuniform electromagnetic beams have been a topic of both theoretical and practical interest for many years, as have singularities in the correlation functions of random scalar wavefields. However, there has been relatively little work done to explore the intersection of these phenomena, namely singularities in the polarization state of partially coherent wavefields. In this paper, we use a simple model of a partially coherent electromagnetic vortex beam to highlight three different ways that one can define polarization singularities in scalar wavefields, one of which has been previously undiscussed.